Determination of Amylose and Amylopectin in Sorghum by Iodine Colorimetric Method - Yun TANG; Haiyan YAN; Yaxiong ZHAO; Dan HUAN; Wenwen ZONG; Feihong SONG (Shipin gongye ke-ji, 2023)
Objective: The content of starch was closely related to the derivative products of sorghum. It was very important to determination of the content of starch, including amylose (Am) and amylopectin (Ap) in sorghum. In this study, the content of Am and Ap was determined by the iodine colorimetry. And conditions of pretreatment and determination were optimized. Method: Using Am and Ap in sorghum as the main object, the content of starch was measured by the iodine colorimetry with different detection methods, including the single wavelength mixed standard method (I), the dual wavelength single standard method (II), and the dual wavelength mixed standard method (III). A series of methodological verifications, such as the precision, detection limit and quantification limit, were compared. And the conditions of pretreatment, such as NaOH and KOH dispersant, gelatinization temperature and time, acetic acid and hydrochloric acid pH regulator, dosage of iodine reagent and color rendering time were optimized. The repeatability verification recovery rate and the determination of common grain samples of the obtained method was also tested, which verified the accuracy of the method. Result: The detection limits and quantification limits of the three methods could meet the requirements of the actual sample measurement range, with detection limits of Am≤0.55 mg/L, Ap≤2.75 mg/L, quantification limits of Am≤1.65 mg/L, Ap≤8.33 mg/L. The absolute error of the accuracy experiments was 0.13% from the mixed standard solution calibration curve, the single standard solution calibration curve error was relatively large (7.47%), thus the mixed standard solution was better to prepare the calibration curve. The optimal preprocessing of sorghum: Using NaOH as the dispersant, the gelatinization temperature at 70 ℃ for 10~20 min, with acetic acid or hydrochloric acid as pH regulator, using standard iodine reagent concentration, controlling the coloring time at 20~30 min, the determination results were relatively stable and accurate. The total content of starch was consistent with the starch content in theory, and it had a good repeatability and recovery (80%~120%). Conclusion: In summary, the dual wavelength mixed standard method of iodine colorimetry was a best method for measuring the content of Am and Ap in sorghum, and it was more suitable for the determination of actual samples in crops.